Influenza A as a True Zoonotic Pathogen: Transmission through Reservoir Hosts - Rabani, Neyazi Ghulam; Saken, Khaidarov; Mohammadi, Mohammad Hamid; Hujatullah, Mukhlis; Modaqeq, Taibullah (Journal for Research in Applied Sciences and Biotechnology, 2024)
Influenza A virus (IAV) represents a considerable global health threat due to its rapid mutation rates and broad host range, facilitating cross-species transmission and enabling the virus to evade immune defenses. This review explores the molecular mechanisms underlying IAV's pathogenicity, focusing on its zoonotic potential through reservoir hosts, such as wild birds and swine. The virus's ability to undergo antigenic shift and drift allows it to continually adapt to new hosts and environments, posing challenges for control and treatment. Current antiviral therapies are limited by the emergence of resistant strains, underscoring the necessity for innovative vaccine development and treatment strategies. By examining IAV's molecular evolution, immune evasion tactics, and transmission dynamics, this review highlights the critical need for enhanced surveillance, improved therapeutic options, and international cooperation to mitigate future outbreaks. A deeper understanding of these processes is essential to inform public health efforts and combat the persistent threat of IAV.